2018
DOI: 10.4103/ortho.ijortho_556_16
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Models in Planning of Revision Hip Arthroplasty with Complex Acetabular Defects

Abstract: Background:Careful preoperative planning in revision cases with complex acetabular defects is crucial for optimal surgery outcome. However, in many cases, computed tomography (CT) scans cannot give a clear understanding of the pelvic destruction. Three-dimensional (3D) models-based on CT data can help surgeon in planning of complex acetabular reconstruction.Materials and Methods:We used 3D plaster pelvic models in 17 revision cases. There were 5 patients with Paprosky II C acetabular defects, 2 patients with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
1
10
0
4
Order By: Relevance
“…Previous study showed preoperative 3D planning technology improved the accuracy of implant position in primary THA [10]. However, application of 3D simulation and model to assist TM cup and augments positioning in revision THA was rarely reported [11, 12]. We aimed to evaluate the advantages and disadvantages of this technology and to provide suggestions for its clinical application in revision THA with complex acetabular defect.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed preoperative 3D planning technology improved the accuracy of implant position in primary THA [10]. However, application of 3D simulation and model to assist TM cup and augments positioning in revision THA was rarely reported [11, 12]. We aimed to evaluate the advantages and disadvantages of this technology and to provide suggestions for its clinical application in revision THA with complex acetabular defect.…”
Section: Introductionmentioning
confidence: 99%
“…Marongiu et al 14 proposed a 3D printed model to help evaluate the fracture pattern and plan for fixation, this has also been proposed in difficult revision arthroplasty scenarios. 15 However, there are cost and time implications with these techniques and they may not be readily available in all centres.…”
Section: Discussionmentioning
confidence: 99%
“…8 3D printed custom triflange components are commonly used for revision THA in the setting of pelvic discontinuity and severe acetabular bone loss, providing an efficient alternative when standard instrumentation does not suffice. 59…”
Section: Patient-specific Implantsmentioning
confidence: 99%